ANALISIS EFEKTIVITAS DAN EFISIENSI PEMUNGUTAN PBB PERKOTAAN ATAS IMPLEMENTASI KEBIJAKAN SUNSET POLICY PBB PERKOTAAN DI KOTA MALANG (Studi Pada Badan Pelayanan Pajak Daerah Kota Malang) - Anas Zul Munir (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of this descriptive qualitative research is to measure the effectiveness and efficiency on the collection of Urban Land and Building Tax according to implementation of Sunset Policy in Urban Land and Building Tax in the city of Malang. This study was conducted at the Local Tax Service Office in the city of Malang. The data of this study were obtained from in-depth interviews and related documents, which were the compared for analysis and concluded. The results of the research indicate that BP2D of the city of Malang has collected Urban Land and Building Tax according to sunset Policy in Urban Land and Building Tax effectively. However, there are inefficiency that requires improvement.Keywords: effectiveness, efficiency, taxation, tax collection, local tax, urban land and building tax